The spatiality of housing market volatility and selective migration - Ferrari, Ed; Rae, Alasdair (Town planning review, 2013)
There are longstanding concerns about volatility in the UK housing market. The price volatility of the market at a national level has been the subject of significant political and academic attention. At the same time, the housing market has become increasingly spatially differentiated. This paper seeks to connect issues of housing market change and differentiation to the separate literature on demand and mobility processes. The paper begins by considering the nature of price changes in the UK housing market over the past 40 years. The emergence of widening regional disparities in house prices since the 1980s is remarked upon and a number of supply- and demand-side drivers of the housing market and of volatility are discussed. The paper then focuses on the potential role of residential mobility, particularly selective migration, between areas of similar socioeconomic characteristics in exacerbating market differentials. It concludes with a number of policy suggestions, notably that there remains an important role for demand-side responses to volatility and for sub-regional planning for housing in the UK.